Time Trends and Projected Obesity Epidemic in Brazilian Adults Between 2006 and 2030 - De Moraes-Ferrari, G (Nature Research, 2022)
We examined time trends and projected obesity epidemic in Brazilian adults between 2006 and 2030 by sex, race/skin color, educational attainment, and state capitals. Self-reported body weight and height of 730,309 adults (≥ 18 years) from the Vigitel study were collected by telephone interview between 2006 and 2019. A multinomial logistic regression model was used to predict the prevalence of body mass index (BMI) categories as a function of time by 2030. The prevalence of obesity increased from 11.8% in 2006 to 20.3% in 2019. The projected prevalences by 2030 are estimated to be 68.1% for overweight, 29.6% for obesity, and 9.3% for obesity classes II and III. Women, black and other minority ethnicities, middle-aged adults, adults with ≤ 7 years of education, and in Northern and Midwestern capitals are estimated to have higher obesity prevalence by 2030. Our findings indicate a sustained increase in the obesity epidemic in all sociodemographic subgroups and across the country. Obesity may reach three out of 10 adults by 2030. © 2022, The Author(s).